Physico-biochemical characteristics of fetal fluids in uterine torsion affected buffaloes - DEOSI, H S; DHALIWAL, G S (The Indian Journal of Animal Reproduction, 2023)
Physical and biochemical characteristics of both allantoic and amniotic fluids of 19 uterine torsion affected buffaloeswere compared with those of 13 dystocia other than uterine torsion and 8 normally calving buffaloes. In the torsion affectedbuffaloes, colour of allantoic fluid varied from reddish to dark brown (28.5% to 35 .6%, respectively) while the colour of amnioticfluid was dirty white in 45.4 % cases. The allantoic fluid of uterine torsion affected buffaloes had significantly higher (P
Keywords: Buffalo; uterine torsion; fetal fluids; dystocia